Health risk assessment and metal contamination in fish, water and soil sediments in the East Kolkata Wetlands, India, Ramsar site - Kumar, Neeraj; Chandan, Nitish Kumar; Bhushan, Shashi; Singh, Dilip Kumar; Kumar, Satish (Scientific reports, 2023)
East Kolkata Wetlands (EKW) is an important site for fish culture in sewage-fed areas, which are major receivers of pollutants and wastages from Kolkata. EKW is internationally important as the Ramsar site was declared on Aug 2002 with an area of 125 km 2 . EKW is a natural water body where wastewater-fed natural aquaculture has been practiced for more than 70 years. It is ecologically vulnerable due to the discharge of toxic waste through sewage canals from cities. Assessing the EKW to understand the inflow and load of the toxic metal (s) in fish, water, and sediments samples is essential. The field (samples collection from 13 sites) and lab (determination of toxic level of metals) based research were carried out to assess metal toxicity and health risk assessment in EKW. The levels of eighteen metals (18), namely Chromium, Vanadium, Cobalt, Manganese, Copper, Nickel, Zinc, Silver, Molybdenum, Arsenic, Selenium, Tin, Gallium, Germanium, Strontium, Cadmium, Mercury, and Lead, were determined using Inductively coupled plasma mass spectrometry (ICP-MS) in five fish tissues viz. muscle, liver, kidney, gill and brain, along with the water samples and soil sediments in 13 sampling sites. The bioaccumulation and concentration of metals in fish tissues, soil sediments, and water samples were well within the safe level concerning the recommendation of different national and international agencies except for a few metals in a few sampling sites like Cd, As, and Pb. The geoaccumulation index (Igeo) was also determined in the soil sediments, indicating moderate arsenic, selenium, and mercury contamination in a few sites. The contamination index in water was also determined in 13 sampling sites. The estimated daily intake (EDI), reference dose (RfD), target hazard quotient (THQ), slope factor and cancer risk of Cr, Mn, Co, Ni, Cu, Zn, As, Se, Cd, Pb and Hg from fish muscle were determined. Based on the results of the present investigation, it is concluded that fish consumption in the East Kolkata Wetland (EKW) is safe. The effects of bioaccumulation of metals in muscle tissue were well within the safe level for consumption as recommended by WHO/FAO.